2013
DOI: 10.3390/s130202164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Mass Loading Sensitivity of Sezawa Wave Mode-Based Surface Acoustic Wave Sensors

Abstract: In this work mass loading sensitivity of a Sezawa wave mode based surface acoustic wave (SAW) device is investigated through finite element method (FEM) simulation and the prospects of these devices to function as highly sensitive SAW sensors is reported. A ZnO/Si layered SAW resonator is considered for the simulation study. Initially the occurrence of Sezawa wave mode and displacement amplitude of the Rayleigh and Sezawa wave mode is studied for lower ZnO film thickness. Further, a thin film made of an arbitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In this work, FEM simulation of a layered SAW device is performed by using COMSOL Multiphysics. The FEM study for different piezoelectric materials has been used, validated and reported by researchers [ 7 , 24 , 25 ]. In first phase of our study, a 2D FEM model of AlN/SiO 2 /Si SAW resonator structure without a sensing layer is investigated.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, FEM simulation of a layered SAW device is performed by using COMSOL Multiphysics. The FEM study for different piezoelectric materials has been used, validated and reported by researchers [ 7 , 24 , 25 ]. In first phase of our study, a 2D FEM model of AlN/SiO 2 /Si SAW resonator structure without a sensing layer is investigated.…”
Section: Problem Formulationmentioning
confidence: 99%
“…SAW sensors are popular because of their real time detection capability, simple fabrication procedure, small size, excellent repeatability, high sensitivity and low cost [ 4 ]. Other than gas sensing applications, the SAW devices also serve a wide range of other applications, such as temperature sensor [ 5 ], pressure sensor [ 6 ] and mass detector [ 7 ] and so forth. Moreover, currently, SAW bio-sensors and microfluidics [ 8 ] are also gaining attention for point-of-care health monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the two previous waves, the energy confinement for Sezawa occur at the boundary between GaN layer and the bulk substrate. In term of sensitivity, Sezawa modes offer a higher sensitivity and higher operating frequency compared to Rayleigh wave with similar configuration [30]. Accordingly, a very sensitive sensor with wide range of frequency covering can be achieved by using a Sezawa-based device.…”
Section: Resultsmentioning
confidence: 99%
“…The device material is quartz with the cut 'poling' rotated about the y-axis, and so resonance is expected around 250 MHz, for its material and geometry, so frequency domain solutions are solved for around this operation frequency, with similar methodology to Ref. [14].…”
Section: Fea Modelmentioning
confidence: 99%